A monograph of the neotropical tree Dipteryx odorata (Aubl.) Willd. - Latchford, R (2002)
A monograph of the species Dipteryx odorata has been created for this dissertation. Different sources were consulted to determine the distribution natural, were it has a potential for a long history of use and were it is cultivated. The Description is given for the genus of Dipteryx and D. odorata. The species is mistaken for different species a list of this information was compiled. The relevant ecological data and uses of the timber and seeds of D. odorata was complied. Finally the wood characteristics were examined for the D. odorata and samples provided for other genera that were cited to have the same common or trade name as D. odorata.